Protective Effect and Mechanisms of Radix Astragali Injection on the Intestinal Mucosa of Rats with Obstructive Jaundice. (14th March 2010) - Xiping, Zhang; Ke, Weng; Yaping, Yu; Hongchan, Zhao; Qihui, Cheng
Abstract : Objective . To research the protective effects and mechanisms of Radix Astragali injection on the intestinal mucosa of rats with obstructive jaundice (OJ). Methods . The rats were randomly divided into sham-operated, model control and Radix Astragali treated group. We observed the pathological changes of intestinal mucosa, expression levels of Bax and NF-κ B proteins, and apoptosis indexes in intestinal mucosa as well as serum NO, MDA and SOD contents, respectively, on 7d, 14d, 21d and 28d after operation. Results . The pathological severity score (on 7d and 14d), apoptotic indexes (on 14d) of the intestinal mucosa and serum MDA content (on 14d) of treated group were significantly lower than those in the model control group (P < .05 ). The serum SOD contents (on all time points) of treated group were significantly higher than those in the model control group (P < .05 ). The sham-operated group (on 21d) of the product of staining intensity and positive rate of Bax protein was significantly lower than model control group (P < .05 ). Conclusion . Radix Astragali injection could protect the intestinal mucosa of OJ rats by increasing the content of SOD, reducing the content of MDA, inhibiting the apoptosis and relieving the pathological changes of intestinal mucosa.